Third Parties as the Subjects of Civil Justice - Kharitonashvili, Nino (Journal of Law, 2017)
The paper considers the development of the third-party institute in civil proceedings and its value for implementation of the right of access to court. It includes comparative analysis of the third parties stipulated in the civil procedures of civil law countries - European Union, Germany, Italy, France and common law countries – UK, USA, Canada and Australia. The article also compares the third persons envisaged in the project “The International Rules of Civil Procedure" of the American Law Institute (ALI) and the International Institute for the Unification of Private Law (UNIDROIT) and in the Civil Code of Georgia. The paper considers the issue about define the type and quality of influence to be exerted by judgment on persons’ rights to involve them in trial in the Civil Procedures Code of Georgia. The paper suggests introduction of the term , intervention” in the Civil Procedure Law of Georgia and differentiation of the kinds of intervention in accordance with the continental (civil) law reflecting the interference of a third party in the civil proceedings. For avoiding intervention of the persons, whose rights and obligations are not impacted by the judgement, the paper, at stipulation of international practice, recommends introduction of the “amicus curiae” procedural mechanism in Civil Procedure Law.